Development of the uno chemical card game as a learning medium on the periodic system of elements for high school students - Yeltika Afria Ningsih; Iswendi Iswendi (Jurnal Pijar Mipa, 2023)
This study aims to develop a chemical uno card game as a learning medium on the periodic system of elements for tenth-grade students and determine its validity and practicality. This type of research is research and development with the Plomp development model, which consists of three stages, namely (1) preliminary research, (2) prototyping stage, and (3) assessment phase. The research subjects were five chemistry lecturers at the Faculty of Mathematics and Natural Sciences, Padang State University, two chemistry teachers, and ten senior high school SMAN 13 Padang students for the 2022/2023 academic year. The research instrument was in the form of one-to-one evaluation interview sheets, media expert validity questionnaires, material expert validity questionnaires, and practicality test questionnaires. Validity data were analyzed using the Aiken'V formula, and practicality data were processed using the percentage formula. The validity value of the media expert was 0.88, and the material expert was 0.85 with the valid category. The results of the practicality analysis by teachers and students are in the very practical category, with respective values ​​of 95.38% and 97%. In conclusion, the uno chemical card game as a learning medium in the periodic system of elements was valid and practical.